Simple rules how to thrive in a complex world - Sull, Donald N. (Boston Houghton Mifflin Harcourt, 2015)
Donald Sull and Kathleen Eisenhardt have spent the last decade working with businesses around the world, and have developed a set of highly effective, tried-and-tested rules to help tackle complex problems, whatever they are. In Simple Rules they share them with you.
Includes bibliographical references (pages 239-272) and index.
Keywords: Simplicity